Empirical Evidence on the Use of ChatGPT in Developing EFL Students’ Reading Comprehension: A Systematic Review - Erwin Kainta; Rahmatul Firdausa Umarella (English Education:Journal of English Teaching and Research, 2026)
This study presents a systematic review of recent empirical research on the use of ChatGPT in developing EFL students’ reading comprehension. The increasing integration of AI tools in language education has raised the need to synthesize evidence regarding their pedagogical effects, particularly in reading instruction. Despite growing scholarly interest in AI-assisted language learning, synthesized evidence specifically addressing ChatGPT’s role in EFL reading development remains limited. Accordingly, this review aims to (1) identify the empirical evidence on ChatGPT use for EFL reading comprehension and (2) explore the reported effects of ChatGPT on EFL students’ reading comprehension. Using a PRISMA-guided selection process, 12 empirical studies published between 2024 and 2025 were included based on established inclusion criteria. The findings indicate that the available evidence is dominated by experimental and quasi-experimental designs, supported by surveys, interviews, and benchmarking studies. Across the reviewed articles, ChatGPT use is consistently associated with improvements in reading comprehension, as well as gains in reading proficiency and competency, main-idea comprehension, inferencing, critical reading and contextual understanding. The review also highlights the role of ChatGPT in facilitating reading comprehension through instructional support such as text simplification and summarization. Despite these findings, the review is limited by the small number of included studies, the limited methodological diversity, and variations in contextual settings and outcome measures. Future research is recommended to apply standardized reading assessments, longer interventions, and broader participant populations to strengthen generalizable evidence for EFL reading pedagogy.